Risk factors for renal involvement in Henoch-Schönlein purpura - Woo Kyung Kim; Chan Jong Kim; Eun Mi Yang (Elsevier, 2021)
Objective: Henoch-Schönlein purpura is a systemic vasculitis that mainly occurs in children. Renal impairment is a major complication of Henoch-Schönlein purpura, but there is no established predictive marker for renal involvement. Thus, in this study, we investigated the risk factors for renal involvement in children with Henoch-Schönlein purpura. Method: The medical records of children newly diagnosed as having Henoch-Schönlein purpura between 2005 and 2020 were reviewed retrospectively. Selected laboratory data were recorded before treatment initiation. The date and the age at diagnosis; sex; and the presence of arthralgia, gastrointestinal and renal involvement were obtained retrospectively. Results: This study included a total of 186 patients with Henoch-Schönlein purpura. Among them, 36.0% had renal involvement; 28.4% had only microscopic hematuria, 53.7% had non-nephrotic range proteinuria, and 17.9% had nephrotic-range proteinuria during follow-up. The mean age was higher (p = 0.016) and female sex was predominant (p = 0.001) in patients with renal involvement than in those without renal involvement. Blood neutrophil/lymphocyte ratio (p = 0.002) and platelet/lymphocyte ratio (p = 0.002) were significantly higher than that of the patients without renal involvement. No statistically significant differences were observed in the hemoglobin concentration, platelet count, presence of arthralgia, and gastrointestinal involvement between patients with and without renal involvement. Logistic regression analysis revealed female sex (odd ratio = 3.213) and neutrophil/lymphocyte ratio (odd ratio = 1.329) as risk factors for renal involvement. Conclusions: Female sex and high neutrophil/lymphocyte ratio were risk factors for renal involvement in Henoch-Schönlein purpura.